2018
DOI: 10.1021/acs.orglett.8b03138
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and Functional-Group-Tolerant Synthesis of B-Organo BODIPYs

Abstract: Boron-dipyrromethenes (BODIPYs) are one of the most important fluorescent materials. Despite their potential unique properties, however, B,B-fluoro-organo BODIPYs (BFR-BODIPYs) possessing an organo group (R) on the boron center have not been studied in detail, due in part to challenges related to their synthesis. In this paper, a convergent synthesis of BFR-BODIPYs operative under mild conditions is reported. Conversions of the thus-synthesized functionalized BFR-BODIPYs by cross-coupling, condensation, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
10
0
2
Order By: Relevance
“…Previously, we observed higher photostability of 2 than that of 1, which we verified by absorption spectrometry. 3 In the present study, the improved photostability of fluoro-perfluoroalkyl BODIPYs was confirmed using a photobleaching assay. Thus, when 1-3 dissolved in methanol were irradiated with a 500 nm light, the degradation rates of the fluorescence intensities of 2 and 3 were much slower than that of 1; 67%/47%/24% of 2 and 75%/59%/37% of 3 remained after irradiation for 15 min/30 min/60 min, respectively, while only 34%/11%/2% of 1 remained (Fig.…”
Section: Photophysical Properties and Chemical Stabilitysupporting
confidence: 68%
See 3 more Smart Citations
“…Previously, we observed higher photostability of 2 than that of 1, which we verified by absorption spectrometry. 3 In the present study, the improved photostability of fluoro-perfluoroalkyl BODIPYs was confirmed using a photobleaching assay. Thus, when 1-3 dissolved in methanol were irradiated with a 500 nm light, the degradation rates of the fluorescence intensities of 2 and 3 were much slower than that of 1; 67%/47%/24% of 2 and 75%/59%/37% of 3 remained after irradiation for 15 min/30 min/60 min, respectively, while only 34%/11%/2% of 1 remained (Fig.…”
Section: Photophysical Properties and Chemical Stabilitysupporting
confidence: 68%
“…2.1 Synthesis of B,B-fluoro-perfluoroalkyl BODIPYs B,B-Fluoro-pentafluoroethyl BODIPY 3 was synthesized similarly to 2. 3 Thus, BF 2 C 2 F 5 was in situ generated by treating commercially available KijBF 3 C 2 F 5 ] with trimethylsilyl triflate in CH 3 CN and then added to a dichloromethane solution of tetramethyl dipyrromethene and ethyl diisopropyl amine (DIPEA). The coupling reaction was conducted at room temperature for 3 h, affording 3 in 23% isolated yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] The BODIPY derivative C would be useful as a fluorescent material. [8] The boron 1,3-diketonate D works as a biocompatible oxidation catalyst of amyloid peptide under near-infrared light irradiation. [9] On the other hand, examples of the difluoromethylsubstituted borate derivatives have been limited so far.…”
Section: Introductionmentioning
confidence: 99%